Mengapa Indonesia Memerlukan Ilmu Sejarah? Beberapa Gagasan untuk ‘Hilirisasi’ Historiografi - Bambang Purwanto (Faculty of Cultural Sciences, 2020)
AbstractHistory is always considered unable to make a real contribution when dealing with everyday life that demands things that are pragmatic from the practicalities of a science. Through